2005
DOI: 10.1063/1.1938270
|View full text |Cite
|
Sign up to set email alerts
|

Interface trap passivation for SiO2∕(0001¯) C-terminated 4H-SiC

Abstract: Interface trap passivation at the SiO2∕carbon-terminated (0001¯) face of 4H-SiC utilizing nitridation and hydrogenation has been evaluated. The SiO2∕SiC interface, created by dry thermal oxidation on the C face, shows appreciably higher interface state density near the conduction band compared to the (0001) Si face. A postoxidation anneal in nitric oxide followed by a postmetallization anneal in hydrogen results in dramatic reduction of the trap density by over an order of magnitude near the conduction band. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
46
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(57 citation statements)
references
References 22 publications
2
46
0
Order By: Relevance
“…Recently, it was shown that a post oxidation anneal in nitric oxide followed by a post metallization anneal in hydrogen through a platinum gate known to catalyze atomic hydrogen formation resulted in a reduction of the trap density by over an order of magnitude near the conduction band. 9,10 It was suggested that this treatment could eliminate the threefold coordinated atoms responsible for the high interface trap density either by hydrogen passivation or by nitrogen replacement. 10,11 Recent density-functional calculations shed some light on both the atomic-scale oxidation mechanism of 4H-SiC and the nature of possible defects at the SiC/SiO 2 interface.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was shown that a post oxidation anneal in nitric oxide followed by a post metallization anneal in hydrogen through a platinum gate known to catalyze atomic hydrogen formation resulted in a reduction of the trap density by over an order of magnitude near the conduction band. 9,10 It was suggested that this treatment could eliminate the threefold coordinated atoms responsible for the high interface trap density either by hydrogen passivation or by nitrogen replacement. 10,11 Recent density-functional calculations shed some light on both the atomic-scale oxidation mechanism of 4H-SiC and the nature of possible defects at the SiC/SiO 2 interface.…”
Section: Introductionmentioning
confidence: 99%
“…These process resulted in the interface state density of 10 12 eV −1 cm −2 , or less, at about 0.2 eV below conduction band edge [7]. The values shown in Fig.…”
Section: Resultsmentioning
confidence: 72%
“…After the annealing and the system has reached room temperature, the D 2 atmosphere was removed by pumping the system down to ∼10 −5 mbar. The use of hydrogen atmosphere enriched in the deuterium isotope ( 2 H = D) assumes that it mimics the behavior of the 1 H. Platinum (Pt) was chosen as the metal electrode due to its catalytic effect in dissociating H 2 molecules into atomic hydrogen, 10 which is more likely to be incorporated than molecular hydrogen.…”
Section: Methodsmentioning
confidence: 99%
“…4,8 The effect of the incorporation of N was related to both the removal and the passivation of residual C in the dielectric/SiC interface region. [9][10][11] The use of POA in H 2 also led to reduction in D it below the conduction band for n-type 4H-SiC (0001) MOS structures 12 and improve the channel mobility of 4H-SiC (0001) MOSFETs. 13 Moreover, combining POAs in NO and in H 2 using platinum (Pt) as the electrode metal caused a complementary reduction in D it 10,14 and enhanced field-effect mobility in 4H-SiC (0001) MOSFETs 15 compared with only NO or only H 2 annealings.…”
mentioning
confidence: 99%
See 1 more Smart Citation